KONFLIK ANNA FITZGERALD DALAM NOVEL MY SISTERâ€™S KEEPER KARYA JODIE PICOULT - Pantow, Citra (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI)
ABSTRACT â€œMy Sisterâ€™s Keeperâ€ is one of the Jodie Picoultâ€™s masterpieces that was chosen as the object of the writerâ€™s research. This research entitled, â€œAnna Fitzgeraldâ€™s Conflicts in the Novel My Sisterâ€™s Keeper by Jodie Picoult aims to identify Anna Fitzgeraldâ€™s inner and physical conflicts in the story, and the cause and effects to Anna Fitzgerald. The writer used Buehlerâ€™s theory (1998) dealing with conflict style to analyze the inner and physical conflicts of Anna Fitzgerald in the novel. In addition to Wellek and Warrenâ€™s theory (1964) was used to find the relation of literature and psychological aspect by analyzing the causes of the conflict and effects to Anna Fitzgerlad which are successfully depicted by Jodie Picoult in her novel My Sisterâ€™s Keeper. The data were collected from the novel focusing on conflicts by identifying inner and physical conflicts, and the cause and effects to Anna Fitzgerald. The identified data were analyzed by using intrinsic and extrinsic approaches. The Intrinsic approach was used to analyze the plot of the story and the character of Anna Fitzgerald. The extrinsic approach was used to analyze the psychological aspect in this case cause and effect to Anna Fitzgerald. The result of this research reveals that Anna Fitzgerald as the main character in the novel My Ssiterâ€™s Keeper experiences two types of conflicts; inner conflict and physical conflict that affected her life; this inner and physical conflicts are caused by her sisterâ€™s illness that leads to physical, psychological, or mental effects on Anna Fitzgerald and also her behavior.